Seating position, seat belt wearing, and the consequences in facial fractures in car occupants Posição no veículo, uso de cinto de segurança e suas conseqüências nas fraturas de face em ocupantes de carros - Alexandre Siqueira Franco Fonseca; Dov Goldenberg; Nivaldo Alonso; Endrigo Bastos; Guilherme Stocchero; Marcus Castro Ferreira (Clinics, 2007)
INTRODUCTION: Trauma caused by traffic accidents is among the main etiologies involved in the occurrence of facial fractures throughout the world. However, the trauma mechanisms involved are different according to the location where the study was performed, due to different conditions of development, legislation, and culture. A retrospective study was done between February 2001 and July 2006, with the purpose of determining the epidemiology and the mechanisms involved in the occurrence of facial fractures among car occupants in the metropolitan area of São Paulo. METHODS: Data were collected from 297 patients admitted with facial fractures to the emergency room of the Hospital das Clínicas, São Paulo University Medical School. Within this period, 151 individuals had been involved in traffic accidents, among which 56 (37.08%) were inside passenger cars. These were grouped based on the seating position that they were occupying at the time of the accident and the wearing of seat belts. Data concerning the number and location of fracture lines were obtained from the different groups, and a fracture/patient index (F/P I) was calculated to compare and make reference to the impact energy among these groups, for subsequent analysis and discussion. RESULTS: 323 fracture lines occurred among 56 patients who were car occupants. By applying the F/P I, we obtained higher values in the group of rear-seat passengers who were not wearing seat belts (7.23 fractures per patient), followed by the group of drivers not wearing seat belts (6.33 fractures per patient), the group of front-seat passengers not wearing seat belts (5.58 fractures per patient), the group of drivers wearing seat belts (5.54 fractures per patient) and, finally, the group of front-seat passengers wearing seat belts (4.00 fractures per patient). None of the rear-seat passengers was wearing seat belts. CONCLUSION: The data collected indicate that the driver position shows a high incidence of facial fractures, not being effectively protected by the seat belt, although the wearing of seat belts seems to have a protective role against the occurrence of facial fractures in front-seat passengers. It was not possible to evaluate the wearing of seat belts among rear-seat passengers, even though the high incidence of fractures in this group showed its high susceptibility to the occurrence of facial fractures, which highlights the need of taking protective measures against this situation. INTRODUÇÃO: Os traumatismos devidos a acidentes de trânsito estão entre as principais etiologias na ocorrência de fraturas de face em todo o mundo. No entanto os mecanismos de trauma são diferentes, conforme o local onde o estudo foi realizado, devido a condições de desenvolvimento, legislação e cultura 1, 2, 3, 4. Com o objetivo de se conhecer a epidemiologia e os mecanismos envolvidos na ocorrência de fraturas de face em ocupantes de automóveis na região metropolitana de São Paulo, foi realizado um estudo retrospectivo entre Fevereiro de 2001 e Julho de 2006. MÉTODO: Foram coletados dados de 297 pacientes admitidos com fraturas de face na sala de emergência do HC-FMUSP. Destes, 151 indivíduos estiveram envolvidos em acidentes de trânsito sendo que 56 (37,08%) estavam dentro de automóveis. Estes últimos foram agrupados baseados na posição em que estavam sentados no veículo no momento do acidente e no uso de cintos de segurança. Dados referentes ao número e localização dos traços de fratura foram obtidos nos diferentes grupos e um Índice Fraturas/Paciente (IF/P) foi idealizado para comparar e avaliar o impacto nesses grupos, e para posteriormente serem analisados e discutidos. RESULTADO: Ocorreram 323 traços de fraturas nos 56 pacientes ocupantes de carros. Aplicando-se o IF/P obtivemos maiores valores no grupo de passageiros do banco traseiro sem cinto de segurança (7,23 fraturas/ paciente), seguido pelo grupo de motoristas sem cinto de segurança (6,33 fraturas/ paciente), passageiros dianteiros sem cinto de segurança (5,58 fraturas/ paciente), motoristas com cinto de segurança (5,54 fraturas/ paciente) e por último o grupo de passageiros dianteiros com cinto de segurança (4,00 fraturas/ paciente). Nesta amostragem, não houve ocupante do banco traseiro com cinto de segurança. CONCLUSÃO: Baseado nos dados dos pacientes e nos resultados do índice foi realizada uma análise comparando-se a incidência de fraturas de face em diferentes condições dentro de um carro, levando-se em conta a posição do ocupante e o uso do cinto de segurança. Os dados indicam que a posição do motorista apresenta uma incidência elevada de fraturas de face, não oferecendo proteção efetiva mesmo com o uso do cinto de segurança, que parece ter papel protetor contra a ocorrência de fraturas de face na posição do passageiro dianteiro. Não foi possível avaliar o uso do cinto de segurança na posição do passageiro traseiro, mas a alta incidência de fraturas no grupo de ocupantes do banco traseiro sem cinto de segurança mostrou a grande suscetibilidade desta posição à ocorrência de fraturas de face, alertando para a necessidade de se tomar medidas de proteção para esta situação.